Behavioral Mapping as a Basis for the Revitalization Concept of Public Space in the Ampenan Beach Area, Mataram City - Lale Garjita Kusumaring Puji; Rini S. Saptaningtyas; Liza Hani Saroya Wardi; Jauhar Fajrin (Jurnal Lingkungan Binaan Indonesia, 2026)
Physical and tourism-oriented considerations often dominate revitalization projects in historic physical coastal public spaces, while the understanding of users’ spatial behavior remains insufficiently integrated into the design process. This condition risks producing public spaces that are less responsive to local communities’ needs. This study aims to map community behavior to inform the development of a revitalization concept for public spaces in the Ampenan Beach area of Mataram City. A qualitative-descriptive approach was employed through behavioral mapping methods grounded in temporal and spatial observations, supported by visual documentation and archival research. Data analysis identified patterns of activity, spatial use intensity, and the interrelations between user behavior and the site's physical setting. The findings reveal concentrations of informal activities, temporal variations in spatial utilization, and discrepancies between existing spatial design and users’ actual behaviors. These results suggest that behavioral mapping functions not only as an observational tool but also as a conceptual framework for formulating context-sensitive, inclusive, and community-oriented principles of public space revitalization within historic coastal environments. This study is limited by a relatively short observation period and the absence of GIS-based spatio-temporal analysis; therefore, more comprehensive follow-up studies are required to strengthen the findings.